Weight Loss Following Hepatopancreatobiliary Surgery. How Much is Too Much? A Retrospective Cohort Study. (April 2022) - Zhang, Betty H.; Ghazi Faisal, Sanaa; Ruo, Leyo; Simunovic, Marko; Pinto-Sanchez, Maria I.; Serrano, Pablo E.
Background & Aims . Postoperative weight loss is common following hepato-pancreato-biliary (HPB) surgical resections; however, the extent of weight loss and the association with poor outcomes have not been well described. We assessed the average percentage of weight loss and risk factors associated with sustained postoperative weight loss. Materials and Methods . We enrolled patients undergoing major HPB surgical resections from 2011–2016 at a single institution. We evaluated percent change in weight postoperatively, incidence of complications, and nutritional clinical markers at 1, 3, and 6 months postoperatively compared to preoperative baseline. We used multiple logistic regression to evaluate factors associated with significant weight loss (>10% from baseline) at 3 months from surgery. Results . Among 262 patients undergoing HPB surgery, liver surgery patients lost 2.5% of baseline weight at 3 months postoperatively but regained baseline weight by 6 months. Pancreatic surgery patients lost 7.7% at 3 months and were unable to recover their baseline weights at 6 months. Forty-three (16%) patients had major postoperative complications including abdominal abscess (5.3%) and anastomotic leak (3.8%). Patients who experienced major postoperative complications had a greater percentage weight loss at 3 months compared to those without major complications: median 11% (interquartile range (IQR): 7%–15%) vs 4% (IQR: 0%–8%), P < .001. In the multivariable analysis, major postoperative complications were associated with significant weight loss at 3 months (OR 3.39, 95% CI 1.38–8.33). Conclusions . Due to the association of weight loss and major postoperative complications, patients who experience significant weight loss (>10% from baseline) may benefit from nutritional assessment for dietary intervention.